2004
DOI: 10.1007/s00464-002-9267-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of laparoscopic colorectal resection

Abstract: Laparoscopic colorectal surgery performed in experienced centers is safe; the observed morbidity and mortality rates are low and acceptable and compare favorably to those observed after standard open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
2
16
0
3
Order By: Relevance
“…With the development of minimally invasive surgery, these morbidity rates may be reduced. The advantages of smaller incisions, decreased postoperative pain, shorter recovery time, and early return to normal activity, have been well described [6][7][8][9][10]. LAHR can offer a clear advantage over OHR in cases that require mobilization of the splenic flexure by avoiding an upper abdominal incision and its potentially increased respiratory complications [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of minimally invasive surgery, these morbidity rates may be reduced. The advantages of smaller incisions, decreased postoperative pain, shorter recovery time, and early return to normal activity, have been well described [6][7][8][9][10]. LAHR can offer a clear advantage over OHR in cases that require mobilization of the splenic flexure by avoiding an upper abdominal incision and its potentially increased respiratory complications [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive techniques for colorectal surgery have evolved since the early 1990 s. Advantages of the laparoscopic approach in colectomies such as decreased morbidity, postoperative pain, hospital stay, and faster return to normal activity [6][7][8][9][10] have led to the application to other procedures such as reversal of Hartmann's procedure. Several small series have reported successful laparoscopic assisted Hartmann's reversal (LAHR) [11][12][13], and a recent systematic review has confirmed that minimally invasive benefits apply for LAHR [14].…”
mentioning
confidence: 99%
“…Recently reported morbidity rates between 6 and 31% for laparoscopic colorectal surgery are well comparable with our data. This also applies to the reported mortality rates varying between 0 and 4.5% in the published literature [9,10]. No large study has been conducted to investigate the risk factors for perioperative complications undergoing laparoscopic sigmoid resection, and until now most studies have concentrated on only few factors with small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical techniques used were similar to those described by other authors in all the principal phases and according to the standard laparoscopic procedures for colon resection (right and left sides) [8,9]. In all cases, a mechanical bowel preparation was completed.…”
Section: Technical Aspectsmentioning
confidence: 99%